Elastic intramedullary nailing for recurrent radial fracture associated with persistent ulnar bowing deformity in a pediatric patient: a case report - Wenrong Yang; Guangmin Pu; Zhigang Zhao; Shuchun Yang; Zhijun Chen; Jincai Liu; Dan Wang (Frontiers in Pediatrics, 2026)
Background Pediatric forearm bowing fracture is an occult incomplete injury with a high misdiagnosis rate. Persistent ulnar bowing deformity is a potential risk factor for recurrent radial fracture due to altered forearm biomechanical stress distribution, and unified management protocols for this combined injury remain lacking. This case report describes the diagnosis and treatment of an 8-year-old girl who sustained a second ipsilateral radial fracture four years after an initial forearm trauma accompanied by ulnar bowing deformity at 4 years old, aiming to provide practical clinical evidence and generate preliminary treatment hypotheses for this clinical scenario. Case presentation The patient, an 8-year-old girl, first presented at 4 years old with a middle-distal third radial fracture concurrent with ulnar diaphyseal bowing deformity. Initial management consisted of closed manual reduction and splint immobilization, and no corrective intervention was performed for the ulnar bowing deformity. Four years following the initial injury, she fell and sustained a displaced recurrent radial fracture at the middle-proximal third of the same forearm. Closed manipulative reduction and plaster casting failed to sustain adequate fracture alignment, prompting surgical intervention with open reduction and elastic intramedullary nailing to repair the radial fracture; the pre-existing ulnar bowing deformity was left unaddressed intraoperatively. At the two-month postoperative follow-up, elbow and forearm function were fully preserved, with only mild residual forearm angular deformity and no functional deficits noted. No surgical complications occurred, and the family tolerated the mild residual deformity. Conclusions This single case observation generates a preliminary clinical hypothesis rather than universal clinical guidance: Elastic intramedullary nailing serves as a safe and reliable minimally invasive surgical option for children with recurrent displaced radial fractures when conservative treatment yields unsatisfactory reduction maintenance. Additional corrective osteotomy is not indicated for pediatric patients presenting with mild ulnar bowing deformity, normal inner-epiphyseal ulna-radius length ratio. Targeted treatment focused solely on the radial fracture can achieve satisfactory radiological recovery and short-term functional outcomes in this patient population.